Silica aerogel dispersion, sheet, and film

The silica aerogel dispersion in polyvinyl alcohol solution addresses the flexibility and insulation limitations of conventional silica aerogel materials by forming flexible, self-supporting films with enhanced thermal insulation and mechanical strength.

JP2025011929APending Publication Date: 2025-01-24DEXERIALS CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023114356
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-12
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Conventional silica aerogel insulation materials using non-woven fabrics lack flexibility and hinder the thinning of films, limiting their application range and insulation performance.

Method used

A silica aerogel dispersion is formulated with silica aerogel particles distributed in an aqueous solution containing polyvinyl alcohol, which allows for the formation of a self-supporting film without non-woven fabrics, maintaining flexibility and enhancing insulation properties.

Benefits of technology

The silica aerogel dispersion enables the creation of flexible, self-supporting sheets with improved insulation performance by reducing thermal conductivity and maintaining mechanical strength, even when used in thin films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025011929000001
    Figure 2025011929000001
  • Figure 2025011929000002
    Figure 2025011929000002
  • Figure 2025011929000003
    Figure 2025011929000003
Patent Text Reader

Abstract

To provide a silica aerogel particle dispersion that can form a self-supporting film without using a nonwoven fabric and provide a flexible sheet-like heat insulating material.SOLUTION: A silica aerogel dispersion comprises silica aerogel particles dispersed in an aqueous solution containing polyvinyl alcohol.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to silica aerogel dispersions, sheets, and films. [Background technology]

[0002] In recent years, silica aerogel has been attracting attention for its use in thermal insulation due to its unique structure. Due to its unique porous structure, silica aerogel is characterized by the fact that approximately 90% of its mass is occupied by air, and because the pore size is smaller than the mean free path of air, no air convection occurs within the pores, resulting in a thermal conductivity that is smaller than that of air. Many insulation technologies that utilize this feature are known.

[0003] For example, Patent Document 1 discloses a coating material for heat insulation containing a specific amount of silica aerogel, an aqueous emulsion binder, and a polysaccharide. Patent Document 2 discloses a coating material for heat insulation containing silica aerogel, a specific water-soluble binder, and nanofibers. All of these coating materials for heat insulation become heat insulation materials when applied to nonwoven fabric and dried.

[0004] Moreover, Patent Document 3 describes the use of a dispersion containing an aerogel powder containing an aerogel component and silica particles, water, and a surfactant having a specific structure, for use as a heat insulating material. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 6836556 [Patent Document 2] Patent No. 7121595 [Patent Document 3] Patent No. 7024191 Summary of the Invention [Problem to be solved by the invention]

[0006] In conventional insulation materials using silica aerogel, nonwoven fabric is used to form the silica aerogel into sheets. However, the use of nonwoven fabric impairs the flexibility of the sheet, narrowing the range of application of the insulation material and preventing the sheet from being made thinner.

[0007] An object of the present invention is to provide a silica aerogel particle dispersion that can form a self-supporting film without using a nonwoven fabric and can provide a flexible sheet-like insulating material. [Means for solving the problem]

[0008] One aspect of the present invention provides a silica aerogel dispersion in which silica aerogel particles are dispersed in an aqueous solution containing polyvinyl alcohol. Effect of the Invention

[0009] According to the present invention, it is possible to provide a silica aerogel particle dispersion that can form a self-supporting film without using a nonwoven fabric and can provide a flexible sheet-like insulating material.

[0010] Hereinafter, an embodiment of the present invention will be described in detail.

[0011] <Silica aerogel dispersion> The silica aerogel dispersion according to the embodiment of the present invention is a dispersion in which silica aerogel particles are dispersed in an aqueous solution containing polyvinyl alcohol.

[0012] Silica aerogel particles refer to silica gel particles composed of a microporous solid with a gas as the dispersed phase. In general, the inside of silica aerogel has a mesh-like microstructure, and has a cluster structure in which particulate aerogel components of about 2 nm to 20 nm are bonded. Between the skeletons formed by this cluster structure, there are pores of less than 100 nm. As a result, silica aerogel has a three-dimensional microporous structure.

[0013] In order to prevent the performance of the silica aerogel from deteriorating due to moisture absorption, the silica aerogel is preferably a hydrophobic silica aerogel having hydrophobic groups on its surface. Specifically, the silica aerogel is made hydrophobic by bonding the tri-substituted silyl groups represented by the following formula to its surface.

[0014] [ka] In the formula, R1, R2, and R3 may be the same or different and are selected from alkyl groups having 1 to 18 carbon atoms or aryl groups having 6 to 18 carbon atoms, and are preferably methyl, ethyl, cyclohexyl, or phenyl.

[0015] As the porosity of silica aerogel increases, the number of air holes of several tens of nanometers that inhibit the mean free path increases, and the thermal conductivity decreases. If silica aerogel has hydrophobic groups on its surface, water is prevented from seeping into or penetrating the pores even when dispersed in an aqueous medium. This means that silica aerogel can maintain its inherent high porosity even in the form of a film or sheet, and can therefore exhibit excellent thermal insulation performance.

[0016] Silica aerogel is particulate, and the average particle size is preferably 1 μm to 50 μm, more preferably 1 μm to 25 μm, and even more preferably 1 μm to 10 μm. If the average particle size is too small, the total particle gap ratio increases, and the ratio of nano-sized pores in the silica aerogel decreases. On the other hand, if the average particle size is too large, the size of the particle gap increases, and air convection occurs between the large gaps, which may reduce the insulation effect.

[0017] The silica aerogel particles may be appropriately synthesized or may be commercially available, such as aerogel particles (MT-1100, manufactured by Cabot Corporation).

[0018] The content of silica aerogel particles is not particularly limited. The content of silica aerogel particles is, for example, 20% by mass or more and 80% by mass, preferably 30% by mass or more and 70% by mass or less, more preferably 40% by mass or more and 60% by mass or less, based on the total mass of the solid content in the silica aerogel dispersion. When the content of aerogel is 20% by mass or more and 80% by mass, excellent heat insulating performance can be exhibited.

[0019] Polyvinyl alcohol (hereinafter referred to as PVA) is a water-soluble polymer having hydroxyl groups, obtained by saponifying polyvinyl acetate obtained by polymerizing vinyl acetate monomer.

[0020] The degree of saponification of the PVA is not particularly limited, but is preferably 75 mol% to 100 mol%, more preferably 80 mol% to 97 mol%, and even more preferably 85 mol% to 92 mol%. Here, the degree of saponification means the ratio of the number of vinyl alcohol units to the total number of vinyl alcohol units and vinyl ester units in the PVA.

[0021] The degree of polymerization of PVA is not particularly limited, but is preferably from 200 to 4000, more preferably from 400 to 4000, and further preferably from 1500 to 3500. Here, the degree of polymerization of PVA refers to the average degree of polymerization of PVA measured in accordance with the description of JIS K6726-1994.

[0022] The PVA may be modified with a carboxylic acid (hereinafter referred to as carboxylic acid modified). Here, the carboxylic acid modified PVA (hereinafter referred to as carboxylic acid modified PVA) refers to PVA in which ester groups are generated by condensation reaction between hydroxyl groups of the PVA and carboxyl groups of an unsaturated carboxylic acid compound.

[0023] The modification rate of the carboxylic acid-modified PVA is optional, but is usually in the range of 0.01 to 40 mol%, preferably 0.1 to 30 mol%. Here, the modification rate of the carboxylic acid-modified PVA means the introduction rate of the unsaturated carboxylic acid compound in the carboxylic acid-modified PVA. The modification rate of the carboxylic acid-modified PVA is expressed as (molar number of unsaturated carboxylic acid vinyl units) / (molar number of vinyl alcohol units+molar number of unsaturated carboxylic acid vinyl units).

[0024] The solvent of the aqueous solution containing polyvinyl alcohol (hereinafter referred to as an aqueous polyvinyl alcohol solution or an aqueous PVA solution) is preferably water or an aqueous solvent containing water. As the water, pure water such as ion-exchanged water, ultrafiltered water, reverse osmosis water, distilled water, or ultrapure water can be used.

[0025] The aqueous solvent may contain an organic solvent other than water. The organic solvent is not particularly limited as long as it is compatible with water, and can be appropriately selected according to the purpose. For example, alcohols such as methanol, ethanol, isopropanol, butanol, ethylene glycol, and propylene glycol; ethers such as diethyl ether, tetrahydrofuran, and 1,4-dioxane; ketones such as acetone and methyl ethyl ketone; carboxylic acids such as acetic acid and propionic acid; and nitrogen-containing compounds such as acetonitrile, dimethylformamide, and triethylamine. These may be used alone or in combination of two or more.

[0026] The aqueous polyvinyl alcohol solution (PVA aqueous solution) may contain other components according to the purpose, such as surfactants, polymers, chelating agents, builders, organic acids, pH adjusters, solvents, defoamers, disinfectants, preservatives, colorants, and fragrances.

[0027] The concentration of the PVA aqueous solution is not particularly limited. The concentration of the PVA aqueous solution indicates the content of PVA in the PVA aqueous solution, and is, for example, 3% by mass or more and 20% by mass or less, preferably 5% by mass or more and 15% by mass or less, and more preferably 8% by mass or more and 13% by mass or less. When the concentration of the PVA aqueous solution is 3% by mass or more and 20% by mass or less, it is easy to form a PVA film.

[0028] The silica aerogel dispersion of this embodiment may optionally contain an aqueous emulsion. Here, the aqueous emulsion refers to a dispersion or dissolution of a resin monomer or a low molecular weight resin in water or an aqueous solvent containing water. The aqueous solvent may be an aqueous solvent that may contain an organic solvent other than the water described above.

[0029] Examples of the aqueous emulsion include resin emulsions such as urethane resin, acrylic resin, styrene / acrylic copolymer resin, and vinyl acetate copolymer resin obtained by copolymerizing vinyl acetate with ethylene, versatic acid vinyl ester, ethylenically unsaturated carboxylic acid, vinyl chloride, (meth)acrylic acid alkyl ester, etc. These may be used alone or in combination of two or more kinds.

[0030] The content of the aqueous emulsion is not particularly limited, but for example, the content of the aqueous emulsion having a solid content concentration of 30% to 60% by mass in the silica aerogel dispersion is preferably 5% to 30% by mass, more preferably 10% to 25% by mass, and even more preferably 13% to 23% by mass.

[0031] The silica aerogel dispersion of this embodiment may optionally contain fibers, where the fiber refers to an object having an aspect ratio of 10 or more, which is the ratio of the average fiber length to the average fiber diameter (the diameter in the case of a substantially circular cross section, or the diameter of a circle having the same cross-sectional area as the rectangular cross section).

[0032] The average fiber length of the fibers is not particularly limited, but from the viewpoint of increasing the strength of the product obtained from the silica aerogel dispersion, it is preferably from 50 μm to 1500 μm, more preferably from 100 μm to 1000 μm, and even more preferably from 150 μm to 700 μm.

[0033] The fiber diameter of the fibers is not particularly limited, but from the viewpoint of increasing the strength of the product obtained from the silica aerogel dispersion, it is preferably from 1 μm to 100 μm, more preferably from 3 μm to 50 μm, and even more preferably from 5 μm to 15 μm.

[0034] Examples of fibers include inorganic fibers such as glass fibers, carbon fibers, and metal fibers, and synthetic fibers such as polyester fibers, polybenzoxazole fibers, acrylic fibers, and polyamide fibers. These may be used alone or in combination of two or more. Among these, inorganic fibers such as glass fibers and carbon fibers, and synthetic fibers such as polyester fibers and polyamide fibers are preferred, and glass fibers are more preferred, in terms of increasing the strength of the product obtained from the silica aerogel dispersion.

[0035] The fiber content is not particularly limited, but is, for example, preferably 0.1% by mass or more and 10% by mass or less, more preferably 0.5% by mass or more and 5% by mass or less, and even more preferably 1% by mass or more and 3% by mass or less, in the silica aerogel dispersion.

[0036] The silica aerogel dispersion of this embodiment preferably contains a defoaming agent. Here, the defoaming agent refers to an additive that is added to prevent foaming or to eliminate foam that has been formed. When silica aerogel is dispersed in an aqueous polyvinyl alcohol solution, the result is often a whipped dispersion that contains a large amount of bubbles, so by using such a defoaming agent, the generation of these bubbles can be prevented or eliminated.

[0037] Examples of the defoaming agent include animal and vegetable oil-based, fatty acid-based, polyether-based, acetylene-based, fluorine-based, silicone-based, mineral oil-based, and phosphoric ester-based defoaming agents. These may be used alone or in combination of two or more. Among these, polyether-based or acetylene-based defoaming agents are preferred, and acetylene-based defoaming agents are more preferred.

[0038] The acetylene-based antifoaming agents include acetylene glycols, their alkylene oxide adducts, and acetylene alcohols.

[0039] Specific examples of these include Surfynol 104 (manufactured by Nissin Chemical Industry Co., Ltd., Surfynol is a registered trademark, the same applies below), Surfynol 420, Surfynol 440, Surfynol 465, Olfine B (manufactured by Nissin Chemical Industry Co., Ltd., Olfine is a registered trademark, the same applies below), Olfine AF-103, Olfine PD-002W, Olfine AF-300, Olfine SPC, and Olfine E1004.

[0040] The content of the defoaming agent is not particularly limited, but is preferably 0.01% by mass to 5.0% by mass, more preferably 0.5% by mass to 4.0% by mass, and even more preferably 0.1 to 3.0% by mass, based on the silica aerogel dispersion. If the content of the defoaming agent is less than 0.01%, the effect of the defoaming agent may not be fully exerted, while if it exceeds 5.0% by mass, the properties of the dried film may be adversely affected.

[0041] In the silica aerogel dispersion of this embodiment, as described above, the silica aerogel particles are dispersed in an aqueous solution containing PVA, so that a free-standing film can be formed without using a nonwoven fabric. In addition, a sheet obtained using such a silica aerogel dispersion has heat insulating properties without losing flexibility because no nonwoven fabric is used. Therefore, the silica aerogel dispersion of this embodiment is useful for forming a sheet or a thin film of a heat insulating material.

[0042] In the silica aerogel dispersion of the present embodiment, as described above, when the saponification degree of PVA is 75 mol% or more and 100 mol% or less, the thermal conductivity of the sheet or film obtained by using the silica aerogel dispersion can be reduced. Also, when the saponification degree of PVA is 85 mol% or more and 92 mol% or less, the thermal conductivity of the sheet or film can be further reduced. Therefore, the silica aerogel dispersion of the embodiment can improve the heat insulation of the obtained sheet or film.

[0043] In the silica aerogel dispersion of the present embodiment, as described above, when the polymerization degree of PVA is 200 or more and 4000 or less, the thermal conductivity of the sheet or film obtained by using the silica aerogel dispersion can be reduced. In addition, when the polymerization degree of PVA is 1500 or more and 3500 or less, the thermal conductivity of such a sheet or film can be further reduced. Therefore, the silica aerogel dispersion of the embodiment can improve the heat insulation of the obtained sheet or film.

[0044] In the silica aerogel dispersion of the present embodiment, as described above, the PVA is modified with a carboxylic acid, so that the thermal conductivity of the sheet or film obtained by using the silica aerogel dispersion can be further reduced. Therefore, the silica aerogel dispersion of the present embodiment can further improve the heat insulation of the sheet or film obtained.

[0045] As described above, the silica aerogel dispersion of the present embodiment contains an aqueous emulsion, which acts as a binder in the silica aerogel dispersion, making the silica aerogel less likely to separate, and improving the coatability of the silica aerogel dispersion when producing a sheet or film from the silica aerogel dispersion.

[0046] In addition, the effect of including such an aqueous emulsion can suppress the deterioration of the heat insulating properties of the sheet or film obtained using the silica aerogel dispersion, which is caused by including PVA, and can also suppress the deterioration of the mechanical strength and the deterioration of the appearance of the sheet or film.

[0047] As described above, the silica aerogel dispersion of the present embodiment contains fibers, which can improve the mechanical strength of a sheet or film obtained by using the silica aerogel dispersion.

[0048] As described above, the silica aerogel dispersion of the present embodiment contains a defoaming agent, which can suppress bubbles generated by dispersing the silica aerogel in the PVA aqueous solution, thereby improving the coatability of the silica aerogel dispersion when producing a sheet or film from the silica aerogel dispersion.

[0049] In addition, due to the effect of containing such an antifoaming agent, air bubbles are less likely to remain in the obtained sheet or film, which suppresses a decrease in the heat insulating properties of the sheet or film, a decrease in mechanical strength, and a decrease in the appearance of the sheet or film.

[0050] <Sheet> The sheet according to the embodiment of the present invention is made of the above-mentioned silica aerogel dispersion, that is, the sheet according to the present embodiment is made of the above-mentioned silica aerogel dispersion in which silica aerogel particles are dispersed in an aqueous solution containing polyvinyl alcohol.

[0051] The thickness of the sheet is not particularly limited, and is, for example, from 10 μm to 5000 μm, preferably from 50 μm to 5000 μm, and more preferably from 100 μm to 5000 μm.

[0052] The mode of producing the sheet is not particularly limited. For example, the above-mentioned silica aerogel dispersion is applied to a release film treated with silicone release, dried, and then peeled off from the release film to obtain a sheet.

[0053] Since the sheet of the present embodiment is made of the above-mentioned silica aerogel dispersion, the effects of the silica aerogel dispersion of the present embodiment can be obtained. Specifically, a free-standing film can be formed without using a nonwoven fabric, and a sheet having heat insulating properties can be obtained without losing flexibility.

[0054] The sheet of the present embodiment may be one in which the silica aerogel dispersion is applied to a substrate. The substrate refers to a film-like or sheet-like member to which the silica aerogel dispersion is applied.

[0055] The material of the substrate is not particularly limited, and for example, fiber materials such as nonwoven fabric, paper, knitted fabric, woven fabric, resin film, etc. are used. Among these, nonwoven fabric is preferably used as the material of the substrate. The nonwoven fabric is, for example, natural fibers such as cotton, hemp, wool, pulp, etc., and synthetic fibers such as polyester, rayon, polyacrylic acid, etc. These may be used alone or in combination of two or more. Among these, synthetic fibers such as polyester are preferably used.

[0056] The manner in which the silica aerogel dispersion is applied to the substrate is not particularly limited. For example, the silica aerogel dispersion is applied to a substrate such as a polyester nonwoven fabric using a bar coater or the like, and then dried to obtain a sheet in which the silica aerogel dispersion is applied to the substrate.

[0057] In the sheet of the present embodiment, the silica aerogel dispersion is applied to a substrate. In addition to improving the heat insulating properties and strength of the sheet by using the silica aerogel dispersion of the present embodiment, the mechanical strength of the sheet can be further improved by using a substrate.

[0058] <Membrane> The film according to the embodiment of the present invention is printed with the above-mentioned silica aerogel dispersion, that is, the film according to the present embodiment is made of the silica aerogel dispersion in which silica aerogel particles are dispersed in the aqueous solution containing the above-mentioned polyvinyl alcohol.

[0059] The thickness of the film is not particularly limited, and is, for example, from 0.1 μm to 1000 μm, preferably from 1 μm to 500 μm, and more preferably from 10 μm to 100 μm.

[0060] The manner in which the silica aerogel dispersion is printed is not particularly limited. For example, in the same manner as in the case of producing the above-mentioned sheet, the silica aerogel dispersion is printed on a release film treated with silicone release, dried, and then peeled off from the release film to obtain a membrane.

[0061] The film of this embodiment is formed by printing the above-mentioned silica aerogel dispersion, and therefore the effects of the silica aerogel dispersion of this embodiment can be obtained. Specifically, a free-standing film can be formed without using a nonwoven fabric, and a sheet having heat insulating properties can be obtained without losing flexibility. EXAMPLES

[0062] Hereinafter, the present embodiment will be further described using experimental examples. Various tests and evaluations were performed according to the following methods. In the following, "parts" or "%" are by mass unless otherwise specified.

[0063] [Preparation of polyvinyl alcohol aqueous solution] As polyvinyl alcohol (PVA), the polyvinyl alcohols shown in Table 1 below were prepared, and 100 parts of each polyvinyl alcohol was mixed with 900 parts of distilled water and stirred at 80°C for 5 hours to prepare a 10% aqueous solution of each polyvinyl alcohol. [Table 1]

[0064] In Table 1, K-05, K-17C, B-20, B-33, H-17, and H-24 are product numbers of Denka Poval (registered trademark) manufactured by Denka Co., Ltd., KL-05 and KH-17 are product numbers of Gohsenol (registered trademark) manufactured by Mitsubishi Chemical Corporation, and 3-88, 5-88, and 25-88KL are product numbers of Kuraray Poval (registered trademark) manufactured by Kuraray Co., Ltd. Incidentally, 25-88KL is a carboxylic acid-modified polyvinyl alcohol (PVA).

[0065] [Example 1-1] (Preparation of silica aerogel dispersion using PVA aqueous solution) To 100 parts of a 10% aqueous solution of K-05, 10 parts of silica aerogel particles having an average particle size of 8 μm (ENOVA (registered trademark) MT1100, manufactured by Cabot Corporation) and 0.25 parts of an antifoaming agent (Olfine (registered trademark) AF-300, manufactured by Nissin Chemical Industry Co., Ltd.) were added, and the mixture was mixed at 2000 rpm for 10 minutes using a planetary mixer (Thinky Corporation, Awatori Rentaro (registered trademark) ARV-200) to prepare a silica aerogel dispersion.

[0066] [Examples 1-2 to 1-11] In the same manner as in Example 1-1, silica aerogel dispersions were prepared using 10% aqueous solutions of polyvinyl alcohol (PVA) shown in Table 1. In addition, when the dispersions had high viscosity, as shown in Table 2, distilled water was appropriately added to disperse the dispersions.

[0067] [Comparative Example 1-1] A silica aerogel dispersion was prepared in the same manner as in Example 1-1, except that a 5% aqueous solution of hydroxypropylmethylcellulose (Metolose (registered trademark) 65SH-1500, manufactured by Shin-Etsu Chemical Co., Ltd.) was used instead of polyvinyl alcohol (PVA).

[0068] Table 2 shows the compositions of the above Examples 1-1 to 1-11 and Comparative Example 1-1.

[0069] [Table 2]

[0070] [Example 2-1] (Preparation of silica aerogel dispersions using PVA aqueous solutions and aqueous emulsions) 10 parts of silica aerogel particles with an average particle size of 8 μm (manufactured by Cabot Corporation, ENOVA (registered trademark) MT1100) and 0.25 parts of a defoamer (manufactured by Nissin Chemical Industry Co., Ltd., Olfin (registered trademark) AF-300) were added to 40 parts of a 10% aqueous solution of K-05, and the mixture was mixed for 10 minutes at 2000 rpm using a planetary mixer (manufactured by Thinky Corporation, Awatori Rentaro (registered trademark) ARV-200) to disperse the silica aerogel particles in the K-05 aqueous solution. 13 parts of a silicone acrylic emulsion with a solid content concentration of 46% (manufactured by Nissin Chemical Industry Co., Ltd., Chaline (registered trademark) E-370) was added to this dispersion, and the mixture was further dispersed at 1000 rpm for 5 minutes to prepare a silica aerogel dispersion.

[0071] [Examples 2-2 to 2-14] Silica aerogel dispersions of Examples 2-2 to 2-14 were prepared in the same manner as in Example 2-1.

[0072] [Comparative Example 2-1] A silica aerogel dispersion of Comparative Example 2-1 was prepared in the same manner as in Example 2-1.

[0073] [Example 3-1] (Preparation of silica aerogel dispersion containing glass fibers) 10 parts of silica aerogel particles (manufactured by Cabot Corporation, ENOVA (registered trademark) MT1100) with an average particle size of 8 μm and 0.25 parts of a defoamer (manufactured by Nissin Chemical Industry Co., Ltd., Surfynol (registered trademark) AF-300) were added to 40 parts of a 10% aqueous solution of 25-88KL, and 10 parts of distilled water were added. Then, the mixture was mixed for 10 minutes at 2000 rpm using a planetary mixer (manufactured by Thinky Corporation, Awatori Rentaro (registered trademark) ARV-200) to disperse the silica aerogel in the 25-88KL aqueous solution. Then, 1 part of glass fiber (manufactured by Asahi Fiberglass Co., Ltd., MF20JH1-20, average fiber length: 200 μm, fiber diameter: 10 μm) was added and dispersed for 10 minutes at 2000 rpm. To this dispersion, 10.8 parts of an adhesive (Saibinol (registered trademark) UC-809, manufactured by Saiden Chemical Industry Co., Ltd.) having a solid content concentration of 55.6% was added, and the mixture was further dispersed at 1000 rpm for 5 minutes to prepare a silica aerogel dispersion.

[0074] [Examples 3-2 and 3-3] (Preparation of silica aerogel dispersions containing PET and nylon fibers) A silica aerogel dispersion was prepared in the same manner as in Example 3-1, except that one part of the glass fiber was replaced with two parts of PET fiber (manufactured by Shin Nissen Co., Ltd., PET fiber, average fiber length: 514 μm, fiber diameter: 12 to 13 μm) or nylon fiber (manufactured by Shin Nissen Co., Ltd., nylon fiber, average fiber length: 402 μm, fiber diameter: 9 to 10 μm).

[0075] Tables 3 and 4 show the compositions of Examples 2-1 to 2-14, Comparative Example 2-1, and Examples 3-1 to 3-3 carried out above.

[0076] [Table 3]

[0077] [Table 4]

[0078] Next, the obtained silica aerogel dispersion was evaluated as follows.

[0079] (Flexibility assessment) The obtained silica aerogel dispersion was printed on a 50 μm thick PET film treated with silicone release using a metal mask with a square hole of 250 × 250 mm so that the film thickness after drying would be approximately 100 μm. Drying was performed at 60 ° C for 15 minutes, and then at 130 ° C for an additional hour. The obtained sheet was peeled off from the release film and cut into a rectangular sample of 20 mm × 250 mm, and the flexibility of the sheet was evaluated by the following method.

[0080] (Flexibility evaluation method) Stainless steel rods with diameters of 20 mm, 10 mm, 5 mm, and 2 mm were prepared, and the samples cut into strips were wrapped around them to confirm the diameter at which cracks occurred. The flexibility was evaluated according to the following criteria. A rating of 3 points or more was deemed to be suitable for practical use.

[0081] [Evaluation Criteria] 5 points: No cracks at any diameter 4 points: Breaks when wrapped around a rod with a diameter of 2 mm 3 points: Breaks when wrapped around a rod with a diameter of 5 mm 2 points: Wrapped around a rod with a diameter of 10 mm and broken 1 point: When wrapped around a rod with a diameter of 20 mm, it breaks.

[0082] (Thermal conductivity evaluation) The obtained silica aerogel dispersion was printed in the same manner as described above so that the film thickness after drying would be 500 μm. The sheet was first left at 30 ° C for 15 hours, then dried at 60 ° C for 1 hour, and then dried at 130 ° C for 1 hour. The obtained sheet was peeled off from the release film, cut to a size of 200 mm × 200 mm, and six sheets were laminated to a thickness of 3 mm. The laminated sheet was sandwiched between two plates (a heating plate and a cooling plate) and the thermal conductivity during heating of the heating plate was measured using a thermal conductivity measuring device (NETZSCH, HFM (registered trademark)-446). The practically preferable value was 0.04 W / mK or less. The results are shown in Tables 5 to 7.

[0083] [Table 5]

[0084] [Table 6]

[0085] [Table 7]

[0086] From Tables 5 to 7, it can be seen that the silica aerogel dispersions of the examples (Examples 1-1 to 1-11, Examples 2-1 to 2-14, and Examples 3-1 to 3-3) can be used to prepare flexible sheets, have low thermal conductivity, and have high heat insulating performance. On the other hand, the dispersions of hydroxypropyl methylcellulose used in the comparative examples (Comparative Example 1-1 and Comparative Example 2-1) have no problems with flexibility, but have high thermal conductivity and poor heat insulating performance.

[0087] It is also found that polyvinyl alcohol (PVA) with a degree of saponification of 87 to 90 mol% has the lowest thermal conductivity, and that PVA with a degree of polymerization of 1800 to 3300 has the lowest thermal conductivity.

[0088] [Examples 4-1 to 4-3] Each of the silica aerogel dispersions prepared in Examples 2-9, 2-10, and 2-11 was applied to a polyester nonwoven fabric (OL-150S, manufactured by Japan Vilene Co., Ltd.) using a bar coater, dried at 60°C for 15 minutes and then at 130°C for 1 hour to prepare a sheet having a thickness of 100 μm. The flexibility was evaluated in the same manner as described above. The results are shown in Table 8.

[0089] [Table 8]

[0090] Table 8 shows that application to nonwoven fabrics is also possible.

[0091] [Examples 5-1 to 5-3] Each of the silica aerogel dispersions prepared in Examples 2-12, 2-13, and 2-14 was printed on a 188 μm thick PET film with an untreated surface using a metal mask with a square hole of 250 × 250 mm so that the film thickness after drying would be approximately 100 μm. Drying was performed at 60 ° C for 15 minutes, and then at 130 ° C for another hour. The adhesion of the obtained sheet to PET was evaluated by the cross-cut method in accordance with JIS-K5600. In practical use, it is desirable for the score to be 1 point or less. The results are shown in Table 9.

[0092] [Table 9]

[0093] Table 9 shows that it is also applicable as a printed film.

[0094] The above disclosed embodiments include, for example, the following aspects. (Appendix 1) A silica aerogel dispersion obtained by dispersing silica aerogel particles in an aqueous solution containing polyvinyl alcohol. (Appendix 2) 2. The silica aerogel dispersion according to claim 1, wherein the polyvinyl alcohol has a degree of saponification of 75 mol % or more and 100 mol % or less. (Appendix 3) 2. The silica aerogel dispersion according to claim 1, wherein the degree of saponification of the polyvinyl alcohol is 85 mol % or more and 92 mol % or less. (Appendix 4) 4. The silica aerogel dispersion according to any one of claims 1 to 3, wherein the degree of polymerization of the polyvinyl alcohol is 200 or more and 4000 or less. (Appendix 5) 4. The silica aerogel dispersion according to any one of claims 1 to 3, wherein the degree of polymerization of the polyvinyl alcohol is 1500 or more and 3500 or less. (Appendix 6) 6. The silica aerogel dispersion according to any one of claims 1 to 5, wherein the polyvinyl alcohol is modified with a carboxylic acid. (Appendix 7) 7. The silica aerogel dispersion according to any one of claims 1 to 6, comprising an aqueous emulsion. (Appendix 8) 8. The silica aerogel dispersion of any one of claims 1 to 7, containing fibers. (Appendix 9) 8. The silica aerogel dispersion according to any one of claims 1 to 7, further comprising an antifoaming agent. (Appendix 10) 10. A sheet comprising the silica aerogel dispersion according to any one of claims 1 to 9. (Appendix 11) 10. A sheet comprising a substrate and the silica aerogel dispersion according to any one of claims 1 to 9 applied thereto. (Appendix 12) A film obtained by printing a silica aerogel dispersion according to any one of claims 1 to 9.

[0095] Although an embodiment of the present invention has been described above, the present invention is not limited to a specific embodiment, and various modifications and changes are possible within the scope of the invention described in the claims.

Claims

1. A silica aerogel dispersion obtained by dispersing silica aerogel particles in an aqueous solution containing polyvinyl alcohol.

2. 2. The silica aerogel dispersion according to claim 1, wherein the degree of saponification of the polyvinyl alcohol is 75 mol % or more and 100 mol % or less.

3. 2. The silica aerogel dispersion according to claim 1, wherein the degree of saponification of the polyvinyl alcohol is 85 mol % or more and 92 mol % or less.

4. 2. The silica aerogel dispersion according to claim 1, wherein the degree of polymerization of the polyvinyl alcohol is 200 or more and 4000 or less.

5. 2. The silica aerogel dispersion according to claim 1, wherein the degree of polymerization of the polyvinyl alcohol is 1,500 or more and 3,500 or less.

6. 2. The silica aerogel dispersion of claim 1, wherein the polyvinyl alcohol is modified with a carboxylic acid.

7. 10. The silica aerogel dispersion of claim 1, comprising an aqueous emulsion.

8. 10. The silica aerogel dispersion of claim 1, containing fibers.

9. 10. The silica aerogel dispersion of claim 1, further comprising an antifoaming agent.

10. A sheet comprising the silica aerogel dispersion according to any one of claims 1 to 9.

11. A sheet comprising a substrate and the silica aerogel dispersion according to claim 1 applied thereto.

12. A film obtained by printing the silica aerogel dispersion according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Heat-insulating paints and materials

    JP6836556B2

  • Aerogel powder dispersion

    JP7024191B2

  • Heat-insulating paints and materials

    JP7121595B2